Peripheral Blood Biomarkers Associated With Outcome in Non-small Cell Lung Cancer Patients Treated With Nivolumab and Durvalumab Monotherapy - Jiang, Meilin; Peng, Wenying; Pu, Xingxiang; Chen, Bolin; Li, Jia; Xu, Fang; Liu, Liyu; Xu, Li; Xu, Yan; Cao, Jun; Wang, Qianzhi; Li, Kang; et al. (Frontiers in Oncology, 2020)
Background: Selecting patients that potentially benefit from immune checkpoint inhibitors (ICIs) is critical. Programmed death ligand-1 (PD-L1) protein immunohistochemical expression on cancer cells or immune cells and Next generation sequencing based tumor mutational burden (TMB) are the hot spots in studies on ICIs, but there is still confusion in the testing methods. Due to blood samples are much easier for clinical application, many potential peripheral biomarkers have been proposed. This study identify blood parameters that associated with outcome of non-small cell lung cancer (NSCLC) patients with ICIs monotherapy. Materials and Methods: Data of 76 NSCLC patients were analyzed retrospectively. To assess the connection between survival and peripheral blood markers measured before and after treatment, we utilized COX regression model survival analysis and receiver operating characteristic (ROC) curve to assess the markers. Results: In the nivolumab cohort, the optimal cutoff for predicting 11 month overall survival (OS) were 168.13 and 43g/L in Platelet-to-lymphocyte ratio (PLR) and albumin, respectively. When patients are grouped with PLR and albumin the cut-offs, a significant difference in SD-PR vursus PD rate were found between high and low groups, separately. which was not found when grouped by PD-L1 expression. Patients with high PLR (>168.13) or low albumin (<= 43g/L) before ICI had a significantly raised hazard of progression, separately (for PLR, P=0.006; for albumin, P=0.033) and of death (for PLR, P=0.014; for albumin, P=0.009) compared with those patients who had low PLR or albumin level. More importantly, we found that higher PLR (>168.13) after the fourth cycle of ICIs was also an prognostic biomarker, which significantly correlated with shorter OS in both Nivolumab (P=0.046) and durvalumab cohort (P=0.028) . Conclusions: PLR and albumin may help the stratification of high progression and death risk group in advanced NSCLC patients treated with nivolumab and durvalumab monotherapy.